Mencegah Perundungan melalui Program Edukasi dan Sosialisasi di Pondok Pesantren Al Kahf - Vivi Sylvia Purborini; Tikka Dessy Harsanti; Sinda Eria Ayuni (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
Al Kahf Islamic Boarding School has a strong commitment to eradicating bullying in the Islamic boarding school environment. With these efforts, Al Kahf Islamic boarding school continues to strive to create a safe and comfortable environment for its students. Socialization methods are an important key in preventing bullying in Islamic boarding schools. The education and training approach is an effective method for increasing awareness of the negative impacts of bullying and establishing good ethics among students. Through this approach, teachers and educational staff can provide a deep understanding of the importance of good interpersonal relationships, foster empathy, and provide knowledge and skills to resolve conflict positively. Through an education and training approach, Islamic boarding schools can create a safe and supportive environment for students. The importance of socialization in preventing bullying has also been proven effective in forming awareness and ethics for students. However, the active role of caregivers, teachers and Islamic boarding school staff in implementing this socialization method is very important.